Deteksi Antibodi Mycobacterium tuberculosa bovis pada Sapi di Wilayah Kabupaten Buleleng, Bangli, dan Karangasem Provinsi Bali - Putu Gede Widiarsa Putra; Nengah Kerta Besung; Hapsari Mahatmi (Udayana University, 2013)
Bovine tuberculosis (BTB) is one the most widespread zoonotic diseases and has recently reemerged as a major health concern. The disease is caused by the Mycobacterium tuberculosis complex (MTBC) that primarily affects humans as its main host, and that is able to attack more hosts such as domestic animals, pet animals, and wild animals. This Cross-Sectional Study was carried out to determine the seroprevalence of BTB in Districts of Buleleng, Bangli, and Karangasem Province of Bali. One hundred and eighty cow blood samples were collected, and the serological status of BTB was detected using Elisa method. The results showed that the seroprevalence of BTB in District of Bangli was 2.22%, while, those was negative in Districts of Buleleng and Karangasem. The positive seroprevalence of BTB in Bangli indicates that the same research must be conducted throughout the districts in the Province of Bali.